(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
As the international crisis due to the COVID-19 emergence, the President of Brasil denies risks of a pandemic flu and opens to negationists’ propaganda on the effects of the virus. His policy substantially differs from the extraordinary measures commonly adopted, at an international level, in order to contain the epidemic, and it may lead to a general context of inner crisis in the political and legal asset of the Federation. In fact, Brasil is characterized by a peculiar scenario, where Federal Government, Parliament and President don’t always agree and national institutions are often in contrast with the States. Indeed, conflicts between Government and Courts are ongoing for a normative plan to contain the epidemic.